Pannexin 1 Channels Contribute to IL-1β Expression via NLRP3/Caspase-1 Inflammasome in Aspergillus Fumigatus Keratitis. (3rd July 2019) - Yang, Xuejiao; Zhao, Guiqiu; Yan, Junwei; Xu, Rui; Che, Chengye; Zheng, Hengrui; Zhu, Guoqiang; Zhang, Jie
ABSTRACT: Purpose : Pannexin 1 channels are deemed to play important roles in inflammation. However, there is limited information regarding their roles in fungal infection diseases, especially fungal keratitis. This study aimed to investigate the role of pannexin 1 channels in Aspergillus fumigatus ( A. fumigatus ) keratitis. Materials and Methods : Mouse models or immortalized human corneal epithelial cells (HCECs) were infected with or without A. fumigatus for given time. The expression of pannexin 1 channels was tested by qPCR, western blot and immunofluorescence staining. Mice of A. fumigatus keratitis were pretreated with carbenoxolone (CBX) or 2ʹ(3ʹ)-O-(4-Benzoylbenzoyl) adenosine-5ʹ-triphosphate (BzATP) to block or activate the opening of pannexin 1 channels respectively. The clinical score was recorded. Cornea tissues were examined for the downstream signals of pannexin 1 channels, including NLRP3, Caspase-1 and IL-1β, and myeloperoxidase (MPO) by PCR and ELISA. Data were analyzed with commercial data analysis software and a P < 0.05 was considered to be statistically significant. Results : Upon A. fumigatus infection, pannexin 1 expression increased at both the mRNA and the protein levels in mice corneas ( P < 0.05, n = 3). Immunofluorescence indicated that pannexin 1 channels were mainly located in the corneal epithelial layer, and they were upregulated after A. fumigatus infection. In vitro, the same tendency was found at the mRNA and the protein levels in HCECs ( P < 0.05, n = 8). In mouse model, blockage of pannexin 1 channels by CBX caused more severely keratitis. The downstream signals of pannexin 1 channels (NLRP3/Caspase-1/IL-1β) and MPO were down-regulated. Whereas activation the opening of pannexin 1 channels by BzATP reduced corneal infection with increased expression of Caspase-1 and IL-1β. Conclusions : Pannexin 1 channels play important roles in the regulation of progression and leucocytes aggregation during corneal A. fumigatus infection via the NLRP3/Caspase-1/IL-β pathway.